2009
DOI: 10.1115/1.3068296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermomigration on Lead-Free Solder Joint Mechanical Properties

Abstract: Thermomigration experiments were conducted to study the change in mechanical properties of 95.5Sn–4Ag–0.5Cu (SAC405) lead-free solder joint under high temperature gradients. This paper presents some observations on samples that were subjected to 1000°C/cm thermal gradient (TG) for 286 h, 712 h, and 1156 h. It was observed that samples subjected to thermal gradient did not develop a Cu3Sn intermetallic compound (IMC) layer, and we observed disintegration of Cu6Sn5 IMC. On the other hand, samples subjected to is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Disintegration of IMC on hot side was studied in depth by Abdulhamid and Basaran [7]. This experiment confinns previous findings.…”
Section: 5supporting
confidence: 80%
See 1 more Smart Citation
“…Disintegration of IMC on hot side was studied in depth by Abdulhamid and Basaran [7]. This experiment confinns previous findings.…”
Section: 5supporting
confidence: 80%
“…The delamination and the absence of Cll(;Sn5 IMC layer are due to the disintegration of the Cll(;Sn5 IMC into Cu and Sn atoms. 7 UBM delamination on top of solder joint 5 when stressed at -20°C ambient temperature. At -30°C ambient temperature, solder joint 4 shows some Cll(;Sns IMC at the hot (top) side, but not as thick as initial one.…”
Section: Metallurgical Analysismentioning
confidence: 99%
“…The microstructural evolution in Cu/Sn4Ag0.5Cu/Cu solder interconnects has been studied under a thermal gradient of 1000-1200°C/cm [121,122]. It has been found that the two major microstructural differences between TM and isothermal samples were the lack of a Cu 3 Sn layer at both the higher and lower temperature sides, and the thinning of the Cu 6 Sn 5 layer at the higher temperature side for the TM samples.…”
Section: Tm In Sn-based Lead-free Solder Interconnectsmentioning
confidence: 99%
“…Otherwise, the thickness of Cu 3 Sn seemed no change at both the cold end and the hot end. This is because the required Cu mass concentration is not enough to form Cu 3 Sn [12].…”
Section: Effect Of Tm On Interfacial Imcs Morphologiesmentioning
confidence: 97%